1982
DOI: 10.1038/ki.1982.184
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary protein and phosphorus restriction on the progression of early renal failure

Abstract: Three groups of patients with chronic renal failure were studied. Group 1 comprised 25 patients with a mean serum creatinine of 2.18 mg/dl and a mean arterial pressure of 117 mm Hg. Group 2 had 20 patients with a mean serum creatinine of 4.24 mg/dl and a mean arterial pressure of 119 mm Hg. All these patients were kept for 18 to 76 months on a diet containing about 40 kcal/kg, 0.6 g/kg of protein, 700 mg of phosphorus, and 1,000 to 1,500 mg of calcium (orally supplemented). Group 3 comprised 30 patients with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
2

Year Published

1984
1984
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(69 citation statements)
references
References 12 publications
2
64
0
2
Order By: Relevance
“…In man, a recent study has suggested that moderate protein restriction may also delay the progression of renal functional deterioration in patients with early renal failure (41). While careful hemodynamic measurements were not performed in that study, it is attractive to speculate that the protective effect oflow protein feeding resulted from the prevention of hyperperfusion in surviving nephrons in these patients.…”
Section: Discussionmentioning
confidence: 77%
“…In man, a recent study has suggested that moderate protein restriction may also delay the progression of renal functional deterioration in patients with early renal failure (41). While careful hemodynamic measurements were not performed in that study, it is attractive to speculate that the protective effect oflow protein feeding resulted from the prevention of hyperperfusion in surviving nephrons in these patients.…”
Section: Discussionmentioning
confidence: 77%
“…Reducing dietary protein content has also been shown to lessen renal damage in nephrotoxic serum nephritis (31,32) and diabetic nephropathy (33) in rats, and in the lupuslike nephropathy of the New Zealand Black/ New Zealand White mouse (34). In humans, studies in both advanced (35) and early renal failure (36) suggest that moderate protein restriction may retard the rate of deterioration of renal function in patients with a variety of renal diseases. Micropuncture studies of glomerular dynamics in rats 1 wk after 90% ablation of renal mass (3) and in rats with DOC-SALT hypertension (2) confirm that, as in the present study, an important effect of protein restriction is to maintain glomerular hemodynamics at near normal levels.…”
Section: Methodsmentioning
confidence: 99%
“…Observations in the dog with an advanced degree of renal mass reduction have not demonstrated a tendency for renal failure to progress (Bourgoignie et al 1987), so there may be major differences between species in the behaviour of residual nephrons in renal insufficiency. Studies of dietary protein reduction in patients with chronic renal failure have however yielded similar clinical benefits to those observed in animal studies, though the precise role of protein restriction in progressive chronic renal failure remains controversial (Giordano 1982;Maschio et al 1982; Klahr et al 1983;Mitch 1984). Early studies of angiotensin converting enzyme inhibitor therapy in patients with chronic renal disease have shown marked benefits (Taguma et al 1985), however the demonstration of a specific therapeutic advantage of angiotensin converting enzyme inhibitors over and above conventional forms of systemic blood pressure treatment has yet to be demonstrated.…”
Section: Studies In the Nephrotoxic Serum Nephritic Model Of Renal Famentioning
confidence: 99%